The conflict between the Papacy and the German Empire during the seventh century AH / thirteenth century AD and its impact on the Crusader movement - Al–yasari, Hayder khudhair murad; Al-Zahawi, Abbas Abdul Sattar Abdul Qadir (Al-Adab Journal, 2021)
The topic of this research revolves around the conflict between the Papacy and the German Empire during the seventh century AH / thirteenth century AD and its impact on the Crusader movement in the Islamic East. It has become evident to us through this study that this conflict had disastrous consequences for the Crusader movement in the Middle East from two sides. The first aspect is the weakness of the papacy’s role in supporting and encouraging the Crusades against the Islamic East during the seventh century AH / thirteenth century CE due to its preoccupation with the conflict with the German Hohenstaufen family. And the departure of the bulk of the work and thinking of the popes to weaken the Christian power, which they had to direct to strengthening the crusade idea if they wanted to continue it, and the second aspect is the loss of the Crusader idea of ​​its previous spiritual attraction in the eyes of the peoples of Western Europe, after it was shocked by the papacy’s exploitation of the Crusade and its advantages in order to achieve Its political purposes, and it turned out to it to be a mere tool to support the ambitions and Greediness of the Holy See, which had the greatest impact in destroying the Crusades in its original (religious) meaning in the eyes of the people of the European West and weakening the Crusader spirit in Europe.